Evaluating the Safety of Potential Probiotic Enterococcus durans KLDS6.0930 Using Whole Genome Sequencing and Oral Toxicity Study - Li, Bailiang; Zhan, Meng; Evivie, Smith E.; Jin, Da; Zhao, Li; Chowdhury, Sathi; Sarker, Shuvan K.; Huo, Guicheng; Liu, Fei (Frontiers in Microbiology, 2018)
Enterococcus durans KLDS6.0930 has previously been shown to have probiotic potential. However, being a potential clinical pathogen, it becomes necessary to evaluate its safety status for novel potential probiotic use. The purpose of this study is to systematically evaluate the safety of E. durans KLDS6.0930 based on its genomics, phenotypic characteristics and oral toxicity. The complete genome of E. durans KLDS6.0930 was sequenced and analyzed for safety-related genes. Antibiotic susceptibility and the production of harmful metabolites were tested. A 28-day repeated oral dose toxicity test was implemented in rats. In vitro, E. durans KLDS 6.0930 was resistant to five antibiotics, with intrinsic resistances to four antibiotics and no identified genes for the last. E. durans KLDS6.0930 was not hemolytic and virulence factors were nonfunctional in its genome. E. durans KLDS6.0930 produced a small amount of tyramine and phenethylamine; genes encoding tyramine decarboxylase were identified. In addition, genotype and phenotype analyses showed that the strain did not have the ability to generate D-lactic acid, indole or nitroreductase. In vivo, E. durans KLDS6.0930 did not induce adverse effects on the organs, hematological and serum biochemical parameters, or cecal bacterial populations in the oral toxicity test. These results indicate that E. durans KLDS 6.0930 can be safely used as a potential probiotic for human consumption and animal feed.